Automated Communication Tools and Computer-Based Medication Reconciliation to Decrease Hospital Discharge Medication Errors. (July 2016) - Smith, Kenneth J.; Handler, Steven M.; Kapoor, Wishwa N.; Martich, G. Daniel; Reddy, Vivek K.; Clark, Sunday
This study sought to determine the effects of automated primary care physician (PCP) communication and patient safety tools, including computerized discharge medication reconciliation, on discharge medication errors and posthospitalization patient outcomes, using a pre-post quasi-experimental study design, in hospitalized medical patients with ≥2 comorbidities and ≥5 chronic medications, at a single center. The primary outcome was discharge medication errors, compared before and after rollout of these tools. Secondary outcomes were 30-day rehospitalization, emergency department visit, and PCP follow-up visit rates. This study found that discharge medication errors were lower post intervention (odds ratio = 0.57; 95% confidence interval = 0.44-0.74; P < .001). Clinically important errors, with the potential for serious or life-threatening harm, and 30-day patient outcomes were not significantly different between study periods. Thus, automated health system–based communication and patient safety tools, including computerized discharge medication reconciliation, decreased hospital discharge medication errors in medically complex patients.